Value Relevance atas Informasi Akuntansi Sebelum dan Sesudah IFRS pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia - Fidelia Fidelia Fidelia; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
This research objective was to know the adoption of International Financial Reporting Standard (IFRS) increased the value relevance of accounting information in Indonesia. This research was conducted at manufacturing company of basic and chemical sector listed in BEI in period of 2007-2014 with 23 sample companies in 8 year period, so the number of observation become 184.The testing process was divided into two periods that were before and after the adoption of IFRS to see the increase in  and significant of the affect of accouting information in the form of EPS and BVPS to value relevance as reflected in the stock price. The result of this study indicated that the adoption of IFRS in Indonesia in basic industry and chemical manufacturing companies increased the value relevance.